Human Rights Protection in the UN: A General and Institutional Overview (The Former Commission on Human Rights, Human Rights Council, High Commissioner for Human Rights, the International Court of Justice and the Protection of Human Rights) - Lakatos, István (The Universal Protection of Human Rights, 2026)
Abstract: This chapter provides an overview of the role of human rights within the UN Charter, in view of the political motivations of the organisation’s founders. In connection with the creation of the United Nations, it also explores the human rights vision of renowned French jurist René Cassin, particularly his concept of “limited sovereignty.” The majority of the chapter is dedicated to a detailed analysis of the work of the UN’s most prominent intergovernmental human rights body, the Human Rights Council, which replaced the Commission on Human Rights in 2006. Understanding the Human Rights Council’s work is challenging without first exploring the context of the Commission on Human Rights, its predecessor, and its operation during the Cold War. Given the critical role of the UN High Commissioner for Human Rights since 1994 in supporting the UN human rights system, the chapter outlines the establishment and function of the High Commissioner’s mandate, highlighting the main political characteristics of the nine High Commissioners to date. The final section addresses a less frequently discussed topic: the human rights aspects of the International Court of Justice’s work.Keywords: UN Human Rights Council, UN Commission on Human Rights, UN High Commissioner for Human Rights, International Court of Justice, René Cassin, UN Charter